2014
DOI: 10.1152/ajpheart.00022.2014
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor role of cyclooxygenase-1-mediated prostacyclin synthesis in non-insulin-dependent diabetic mice induced by high-fat diet and streptozotocin

Abstract: . Vasoconstrictor role of cyclooxygenase-1-mediated prostacyclin synthesis in noninsulin-dependent diabetic mice induced by high-fat diet and streptozotocin. Am J Physiol Heart Circ Physiol 307: H319 -H327, 2014. First published May 30, 2014 doi:10.1152/ajpheart.00022.2014.-This study tested the hypothesis that in diabetic arteries, cyclooxygenase (COX)-1 mediates endothelial prostacyclin (PGI2) synthesis, which evokes vasoconstrictor activity under the pathological condition. Non-insulin-dependent diabetes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 56 publications
4
48
0
1
Order By: Relevance
“…Previous studies indicate that the levels of these prostaglandins remain unchanged in the coronary vessels of diabetic rats [13], while increased prostacyclin production has been shown in diabetic mice aorta [9]. It has been also shown that prostacyclin, a prostanoid with a wellestablished role of vasodilator, can become a vasoconstrictor in particular cases [19,4]. This implies that the effects of diabetes on vascular function should always be considered with respect to the particular vascular bed, and any comparisons of the results obtained for different vascular beds should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the levels of these prostaglandins remain unchanged in the coronary vessels of diabetic rats [13], while increased prostacyclin production has been shown in diabetic mice aorta [9]. It has been also shown that prostacyclin, a prostanoid with a wellestablished role of vasodilator, can become a vasoconstrictor in particular cases [19,4]. This implies that the effects of diabetes on vascular function should always be considered with respect to the particular vascular bed, and any comparisons of the results obtained for different vascular beds should be made with caution.…”
Section: Discussionmentioning
confidence: 99%
“…First, it could inhibit activation of inflammatory cells during no reflow, thereby decreasing endothelial damage . Second, it could decrease the production of endothelium‐derived NO and prostacyclin and thus improve vascular endothelial function . The observations reported herein are the first demonstration that COX has a role in promoting no reflow in rats.…”
Section: Discussionmentioning
confidence: 65%
“…Using a low dose of streptozotocin with a high-fat fed C57Bl/6J mouse creates a higher level of blood glucose, which is present in both the fasted and fed state. This type 2 diabetic mouse model has been previously used to examine pharmacological interventions, vascular biology and atherosclerosis, cardiomyocyte hypertrophy, and β-cell function (Bansal et al, 2012; Lin et al, 2015; Lv et al, 2010; Mali et al, 2014; Ullevig, Zhao, Zamora, & Asmis, 2011; Wang, Hsu, Lin, & Chen, 2014; Xue, Ding, & Liu, 2010; Zhu et al, 2014). In our studies comparing the effect of diet-induced obesity, type 1 and type 2 diabetes on neuropathy, we found the severity of hyperglycemia was significantly different between the types 1 and 2 diabetic mouse models (Yorek et al, 2015).…”
Section: Rodent Models Of Type 2 Diabetesmentioning
confidence: 99%